A educação especial na formação docente em geografia nas universidades públicas paranaenses: uma análise documental - Oliveira, Maryane Teixeira Jacob de (Universidade Federal de São Carlos, 2023)
The inclusion of Special Education Target Public Students (PAEE) in the common school provokes reflections about the training and performance of teachers of the different degrees. Thus, we raise the following question: Is the area of Special Education being contemplated in the political-pedagogical project and in the curricular organization of the Degree courses in Geography of the Public Institutions of Higher Education (IES) of the state of Paraná? Thus, the general objective was to analyze the training of teachers in undergraduate courses in geography with regard to the propositions of special education in the inclusive perspective. This research has a qualitative approach of documentary character. A total of 15 courses were investigated, nine from state and two federal institutions, distributed throughout the territory of Paraná. The following steps were followed: selection of documents, exploratory reading of the files and application of the documentary analysis script. The collected data were organized and analyzed using the technique of content analysis with the pre- and post-defined categories. The data showed that the teaching model presented by most of the courses is based on the DCNs, in which we identified a teacher capable of working considering the diversity in teaching. Despite this, we note that the textual structure of PPPs presents little or no discussion in relation to the contents of special education. The data of the curricular components showed that the minimum of disciplines and contents required by law on special education is offered, which conflicts considering the formative model that the courses propose to form. We also perceive the rupture of the specific knowledge of geography with the pedagogical knowledge that underlies the formation in licensure, which may not contribute to a teacher training adequate to the context of an accessible education. This demonstrates that the absence of didactic-pedagogical in undergraduate courses will cause special education to remain segregated in the formative curriculum.
Special education in teacher training in geography in public universities of paraná: a documentary analysis
Keywords: Educação especial; Formação inicial de professores; Licenciatura em geografia; Currículo; Special education; Initial teacher training; Geography teaching program; Curriculum; CIENCIAS HUMANAS::EDUCACAO::CURRICULO